2009
DOI: 10.1007/s11661-009-9920-3
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Deformation Behavior of Phase-Reversion-Induced Nanograined/Ultrafine-Grained Austenitic Stainless Steel

Abstract: Materials with submicron to nanometer-sized grains by virtue of their high grain boundary area to grain size ratio provide valuable tools for studying deformation behavior in ultrafine-grained structures. In this regard, the well-known strain-induced martensite transformation and its reversal to the parent austenite phase were used to produce nanograins/ultrafine grains via controlled annealing of heavily cold-worked metastable austenite. The results of the electron microscopy study of phase-reversion-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
71
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 47 publications
1
71
0
Order By: Relevance
“…UFG (Ultrafine-grained) as well as NG (nano-grained) materials have been produced by reversion annealing of AISI 304, AISI 304L, and less stable AISI 301LN and AISI 201 metastable stainless steels, where the material strength is enhanced with a moderate decrease in plasticity. [23][24][25][26][27][28][29] Grain refinement via reversion annealing still draws attention, i.e., Sun et al [30] reported diffusive reversion of strain-induced martensite during annealing in the range of 823 K to 923 K (550°C to 650°C). [30] This paper reports the formation of SIM during the tensile test at different temperatures, and the reverse transformation analysis by the use of DSC, in-situ X-ray diffraction, and dilatometry.…”
Section: Introductionmentioning
confidence: 99%
“…UFG (Ultrafine-grained) as well as NG (nano-grained) materials have been produced by reversion annealing of AISI 304, AISI 304L, and less stable AISI 301LN and AISI 201 metastable stainless steels, where the material strength is enhanced with a moderate decrease in plasticity. [23][24][25][26][27][28][29] Grain refinement via reversion annealing still draws attention, i.e., Sun et al [30] reported diffusive reversion of strain-induced martensite during annealing in the range of 823 K to 923 K (550°C to 650°C). [30] This paper reports the formation of SIM during the tensile test at different temperatures, and the reverse transformation analysis by the use of DSC, in-situ X-ray diffraction, and dilatometry.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In this approach, severe deformation of adequately metastable austenite at room temperature leads to strain-induced transformation of austenite (fcc c) to martensite (bcc a¢). On annealing, the severely deformed strain-induced martensite reverts back to austenite [1][2][3][4] via diffusional or shear reversion mechanism. [5,6] The optimal phase reversion annealing sequence resulted in the structure that was characterized by a combination of high yield strength and excellent elongation of 800 to 1000 MPa and 30 to 40 pct, respectively.…”
mentioning
confidence: 99%
“…[5,6] The optimal phase reversion annealing sequence resulted in the structure that was characterized by a combination of high yield strength and excellent elongation of 800 to 1000 MPa and 30 to 40 pct, respectively. [1] In a diffusional reversion mechanism, the phase reversion process and the ''final'' microstructure are not only a function of diffusion rate in bcc (martensite) and fcc (austenite) phase, but also depend on the martensite structure and density of defects. These two characteristics may accelerate the transformation characteristics or provide an increased number of nucleation sites.…”
mentioning
confidence: 99%
“…[10][11][12][13] The cellular response of NG/UFG austenitic stainless steel is compared with conventional coarse-grained (CG) austenitic stainless steel. Cell culture studies indicated that NG/UFG structure favorably modulates cellular response in terms of initial cell attachment, proliferation, viability, morphology, and spread of fibroblasts, a behavior that is significantly different from the CG structure.…”
Section: Introductionmentioning
confidence: 99%
“…Using adequate energy, perfect samples were formed from both NG/UFG and CG the sheets. [10][11][12][13] In the attempt to identify the effects of NG/UFG structures on cellular response, CG and NG/UFG austenitic stainless steels were simultaneously investigated. Their grain structure and constituent phases were studied by scanning and transmission electron microscopy (TEM) and surface roughness by atomic force microscopy (AFM).…”
Section: Introductionmentioning
confidence: 99%